P-99 Multi-disciplinary palliative care for men living with duchenne: a qualitative interview study. Issue Volume 8: Issue (2018)Supplement 2 (November 2018) - Laidlaw, Sheonad; Carduff, Emma
Abstract : Background: Duchenne Muscular Dystrophy (DMD) is an x-linked, ultra-rare neuromuscular condition affecting 1 in 3600–6000 live male births (Bushby, Finkel, Birnkrant et al ., 2010). Individuals live with an exceptional illness trajectory of prolonged dwindling, frailty and high symptom burden (Landfeldt, Lindgren, Bell et al ., 2014). While it is recognised that a co-ordinated multidisciplinary team approach may increase the survival of those with DMD and improve their quality of life (QoL) (Bushby, Finkel, Birnkrant et al ., 2010), adults are receiving less comprehensive and co-ordinated care compared with those in the paediatric service (Rodger, Woods, Bladen et al ., 2015). Aim: To investigate QoL in adults with DMD living in the West of Scotland (WoS). Methods: The SEIQoL-DW tool was used to assess the five most important elements that contribute to an individual's QoL – these were then used to guide qualitative interviews with six men in the WoS. A thematic analysis was undertaken. Results: Men living with DMD in the WoS described living good lives, but feel 'forgotten' due to perceived gaps in their care: poorly co-ordinated and infrequent health care; lack of multi-disciplinary team input and holistic care; and poor or no access to allied health care professionals, for example physiotherapy and psychological support. Conclusions: Existing guidelines rarely seem to materialise as person-centred care. There are numerous opportunities to introduce palliative care gently, as part of the MDT, early in the illness trajectory and continue in a dynamic manner as time elapses and when trigger points arise. Better co-ordinated multi-disciplinary care, with the inclusion of a palliative care specialist, may be a solution allowing for an early introduction to palliative care and proactive advance care planning.